The Study of Superhydrobobicity of Kapok Fiber and Its Performance - Zol, Nur Akmal Adib; Hussin, Rosniza (Progress in Engineering Application and Technology, 2021)
Kapok fiber is a natural plant fiber which, due to its penetrating hollow light structure and the waxy material surface, provides excellent hydrophobic-oliophilic characteristics. Selectivity nature and sorption capacity of 2 grams of fiber was measured in various forms of oil of different viscosity. The oils used are cooking oil (medium viscosity), lubricant oil (high viscosity), petroleum oil (low viscosity), lubricant oil 2t (high viscosity) and diesel oil (low viscosity), with kapok fiber, which absorbs the highest volume of oil absorbed by lubricating oil. Following the selectivity test, the morphology of raw kapok fiber and the oil absorbed kapok fibers is supposedly analysed using scanning electron microscopy (SEM). The fiber that absorbed different types of oils is relatively quite stable as they show little change in morphology compared to the raw kapok. Kapok fiber shows great potential as oil sorbent on any type of oil owing to its excellent hydrophobicity-oleophilicity characteristic.